Pemanfaatan Media Sosial Dalam Digital Marketing - Amar Naufal Al-kharits; Nazar Maulana; Muhamad Bustomi; Eko Andri Wibowo; Ageng Samudro Ndiko Laksono (Jurnal Sinergi Sistem Informasi Pengabdian Masyarakat, 2025)
The advancement of information technology has transformed the way products are marketed globally, with social media now serving as one of the primary tools in digital marketing strategies. This Community Service Program (PKM) aimed to educate students at SMK YMIK Joglo on how to effectively utilize social media to support digital marketing, whether for personal or business purposes. Held on November 20, 2024, the program employed an interactive approach that included lectures, discussions, case simulations, and hands-on practice using digital platforms such as Instagram and TikTok. Topics covered included an introduction to digital marketing, the fundamentals of personal branding, techniques for creating engaging content, and the use of visual design tools like Canva. The implementation results showed that participants experienced improved understanding of digital marketing concepts and were able to independently create appealing promotional content. The high level of participation during Q&A and practical sessions demonstrated that interactive methods are highly effective for delivering material. This program is expected to serve as a starting point for fostering a digital entrepreneurial spirit among students and encouraging the productive use of social media. Support from the school, supervising lecturer, and guest speakers played a vital role in the program's success. The activity also lays a foundation for future initiatives aimed at enhancing digital literacy in vocational education environments.